Effect of Different Combinations of Manures and Fertilizers on Growth and Yield of Potato (Solanum tuberosum L.) Variety Khumal Seto in Bajhang, Nepal (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
A field experiment was conducted considering different fertilizers and their combination at Bitthadchir Rural Municipality- 2 Syandi, Bajhang district of Nepal during Feb-June, 2024, to find their effect on potato var. Khumal Seto. The field was laid out in randomized complete block design with the treatments: Farmers’ practice (T1), Farmyard manure (T2), Goat manure (T3), Poultry manure (T4), Compost manure (T5), Panchagavya (T6), & Farmyard manure + 50% RDF (T7), which were replicated thrice. Chemical fertilizers were applied as recommended by the government in all the treatments except farmers’ practices. The statistical analysis revealed significant variations among the treatments in days to sprouting, number of branches, and plant heights at 90 DAP at 5% level of significance. Plant height was found to be the highest in poultry manure followed by farmyard manure, and compost manure, with the lowest in farmers' practice. Plant height obtained from panchagavya was statistically similar to that obtained from goat manure. There was no significant difference in the yields among different treatments, except the marketable tuber weight, which was significantly highest in poultry manure. An increase in yield by 33.35, 26.06, and 22.09 percentage were observed in poultry manure, compost manure, and goat manure respectively, when compared to farmers’ practice. Considering both the quality and quantity of potato, poultry manure could be suggested for profitable potato production in the study site.